1979
DOI: 10.1177/002221947901200609
|View full text |Cite
|
Sign up to set email alerts
|

Sociometric Status of Learning Disabled Children in an Integrative Program

Abstract: The sociometric standing of primary-aged learning disabled students was investigated. The setting was a sparsely populated rural area where learning disabled children were mainstrearned in an elementary school in which an "open concept" delivery of services system was in operation. The "special child" stigma was therefore assumed to be significantly reduced. The data support the findings of previous studies on handicapped and normal children; i.e..significant differences were found between the learning disable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

1982
1982
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 10 publications
(11 reference statements)
2
22
0
1
Order By: Relevance
“…Studies have consistently demonstrated that students with LD have lower peer status compared to their non-Ieaming disabled (NLD) peers (Bruininks, 1978;Bryan, 1974Bryan, , 1976Scranton & Ryckman, 1979;Silver & Young, 1985;Siperstein, Bopp, & Bak, 1978;Wiener, 1987). In addition, teachers tend to perceive these students as less socially competent and to have poorer peer relations than NLD peers (Bender & Smith, 1990;Haager & Vaughn, 1995).…”
Section: Emotion and Learning Disabilities Xvllmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have consistently demonstrated that students with LD have lower peer status compared to their non-Ieaming disabled (NLD) peers (Bruininks, 1978;Bryan, 1974Bryan, , 1976Scranton & Ryckman, 1979;Silver & Young, 1985;Siperstein, Bopp, & Bak, 1978;Wiener, 1987). In addition, teachers tend to perceive these students as less socially competent and to have poorer peer relations than NLD peers (Bender & Smith, 1990;Haager & Vaughn, 1995).…”
Section: Emotion and Learning Disabilities Xvllmentioning
confidence: 99%
“…However, the importance of examining the social functioning of students with LD has gained increasing recognition in the field (Hutchinson, Freeman, & Berg, 2004;Wong & Donahue, 2002). Many studies have consistently demonstrated that students with LD have lower peer status as compared to theirNLD peers (Bruininks, 1978;Bryan, 1974Bryan, , 1976Conderman, 1995;Scranton & Ryckman, 1979;Silver & Young, 1985;Siperstein, Bopp, & Bak, 1978;Wiener, 1987) and to be more rejected by their classmates (Stanovich, Jordan, & Perot, 1998;Stone & LaGreca, 1990;Wiener, Harris, & Shirer, 1990).…”
Section: Emotion and Learning Disabilities 26mentioning
confidence: 99%
See 1 more Smart Citation
“…On the negative side, several studies reported that children with disabilities were more likely to be rejected and less likely to be accepted by their nondisabled peers (Bruinicks, 1978;Bryan, 1974Bryan, , 1976Scranton & Ryckman, 1979;Siperstein, Bopp, & Bak, 1978). Jenkins et al (1985) reported no significant differences in the social interaction of children with disabilities in integrated and segregated classes, while the existence of a deficit in peer-related social interactions for these children was reported by Guralnick and Groom (1987).…”
Section: Research Findings On the Social Effects Of Integrationmentioning
confidence: 99%
“…Recent investigations have shown that learning disabled students are also rejected by peers (Bruininks, 1978;Bryan, 1974bBryan, , 1976Scranton & Ryckman, 1979), although their status may be tempered by whether or not they possess other prized attributes such as attractiveness and athletic ability (Siperstein, Bopp, & Bak, 1978).…”
Section: Peer Attitudes Toward Ld Studentsmentioning
confidence: 99%